MANUFACTURING TECHNIQUE OF METAL CERAMIC RESTORATION WITH IMPLANT-ABUTMENT AT GINGIVAL RESORPTION CASE - Paramarta, Galih; Inayati, Eny (Faculty of Vocational Studies, Universitas Airlangga, 2019)
Background: The low levels of patient satisfaction and confidence in the restoration of the gingival resorption results in impaired quality of life in both functional and psychosocial aspects. It is necessary to manufacture a dental restoration to restore the mastication, phonetic, and aesthetic functions associated with soft tissue repair. Manufacture of gingiva ceramic restorations which are believed to be an alternative to restore the aesthetic function and harmonization of the patient's teeth. In terms of manufacturing techniques, this restoration has a level of difficulty in achieving a balance between